Sytuacja społeczno-polityczna w okresie powstania muru berlińskiego według polskich przekazów prasowych - Romański, Mirosław (Acta Universitatis Lodziensis. Folia Historica, 2015)
The article deals with the matter of social-political relations between GDR and the People’s Republic of Poland within the period of building the Berlin Wall in 1961 from the point of view of the Polish press issued officially and unofficially which has been little studied so far. It shows huge differences in opinions and reliability of transferring press information between the official press and the one issued in the West. It involves mainly the relationship of Polish press towards the Berlin Wall and methods and directions of shaping the public opinion. Capturing the subject character of propaganda that was used in showing the relations between GDR and Federal Republic of Germany was also important. That is why analysing the chosen press titles issued within the mentioned period was also necessary for that reason, although it can be stated that defining those relations was not an easy task due to the poor sources (only several press articles).